2019
DOI: 10.7567/1882-0786/ab4233
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the electrical behaviors of Cu/MXene/SiO2/W memristor

Abstract: Electronic synapses with both long-term and short-term plasticity are considered as significant components for constructing brain-inspired computing systems. Research progress on electrical synapses have proved that memristors possess huge similarities with biological synapses. Nevertheless, an effective mean of manipulating the biological properties of memristors is still unclear. In this letter, we propose a memristor and reveal that the compliance current of electroforming plays an active role in tuning sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The initial state of the AMT-based comparator was set to MRS by UV light. Afterward, the V p was Ag/V 2 C/TiO 2 /W (-0.6 V to 1.0 V) --Yes - [138] Ag/Ti 3 C 2 T x /Pt (-10.0 V to 10.0 V) Yes Yes Yes - [135] Al/Ti 3 C 2 T x -ZnO/ITO (-1.0 V to 3.0 V) --Yes - [140] Cu/Ti 3 C 2 /SiO 2 /W (-2.4 V to 2.4 V) Yes -Yes - [136] Al/Ti 3 C 2 /Pt (-3.0 V to 3.0 V) --Yes Yes [76] Al/Ti 3 C 2 @Ag/Pt (-0.2 V to 0.2 V) Yes Yes Yes - [80] Ag/Ti 3 C 2 /SiO 2 /Pt (-1.0 V to 0.5 V) Yes Yes Yes - [142] Al/Ti 3 C 2 T x /Pt (-6.0 V to 6.0 V) Yes Yes Yes Yes [79] applied on the top electrode, while the V q was applied on the bottom electrode. When the pulse voltage of V p or V q is 0 V, p or q is "0".…”
Section: Logic Circuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial state of the AMT-based comparator was set to MRS by UV light. Afterward, the V p was Ag/V 2 C/TiO 2 /W (-0.6 V to 1.0 V) --Yes - [138] Ag/Ti 3 C 2 T x /Pt (-10.0 V to 10.0 V) Yes Yes Yes - [135] Al/Ti 3 C 2 T x -ZnO/ITO (-1.0 V to 3.0 V) --Yes - [140] Cu/Ti 3 C 2 /SiO 2 /W (-2.4 V to 2.4 V) Yes -Yes - [136] Al/Ti 3 C 2 /Pt (-3.0 V to 3.0 V) --Yes Yes [76] Al/Ti 3 C 2 @Ag/Pt (-0.2 V to 0.2 V) Yes Yes Yes - [80] Ag/Ti 3 C 2 /SiO 2 /Pt (-1.0 V to 0.5 V) Yes Yes Yes - [142] Al/Ti 3 C 2 T x /Pt (-6.0 V to 6.0 V) Yes Yes Yes Yes [79] applied on the top electrode, while the V q was applied on the bottom electrode. When the pulse voltage of V p or V q is 0 V, p or q is "0".…”
Section: Logic Circuitsmentioning
confidence: 99%
“…fabricated a two‐terminal memristor of Ag/Ti 3 C 2 T x /Pt structure with the single‐component Ti 3 C 2 T x nanosheets as an active layer, which exhibited threshold resistive switching characteristics and realized the versatile synaptic emulations including paired‐pulse facilitation, post‐tetanic potentiation, short‐term potentiation, and short‐term potentiation to long‐term potentiation transition. [ 135 ] For laminated MXene‐based memristors, a strategy of preparing binary layered structures is to first deposit an oxygen‐containing functional layer (e.g., SiO 2 [ 136,137 ] and TiO 2 [ 138 ] ) onto the bottom substrate by physical vapor deposition (PVD), and then fabricate a layer of MXenes on the oxygen‐containing functional layer. Another strategy is proposed by Yang et al., which obtains a layer of MoO x at the surface of Mo 2 C by thermal oxidation and affords a vertical MoO x /Mo 2 C heterostructure.…”
Section: Mxene‐based Memristive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35,36 ] To date, Yan et al. and Wang et al, demonstrated memristor bipolar resistive switching with MXene flakes for the artificial bio‐synapse applications [ 37,38 ] while Chen et al. reported TS‐based memristor for the artificial neuron device application.…”
Section: Introductionmentioning
confidence: 99%
“…Such an attractive trait relies on its unique, non-volatile resistive switching (RS) characteristic that can vary between high and low resistive states. However, resistance states of the memristor devices usually fluctuate during different write cycles, even with the same external stimulus [ 27 ]. One novel approach to address this issue is to introduce an additional MXene (i.e., Ti 3 C 2 ) layer into the silicon dioxide (SiO 2 )-based memristor device to improve its repeatable RS characteristic [ 28 ].…”
Section: Introductionmentioning
confidence: 99%